Korelasi Kebijakan Otoritas Gereja Kristen Sumba Dengan Pencegahan Perkawinan Anak di Kabupaten Sumba Timur - I Ketut Satria Wiradharma Sumertajaya; Jonker Sihombing; Dianita Aprissa L. Taranau; Arniyati Danggamesa (Fakultas Hukum, Universitas Warmadewa, 2026)
East Sumba Regency is one of the regions in Indonesia with a high rate of child marriage. One of the strategies for preventing underage marriage formulated by the government in the National Strategy for Women and Children Protection (STRANAS PPA) is strengthening stakeholders at the national and regional levels. One stakeholder that can play a role in preventing it is religious institutions. In East Sumba, 78.6% of the population adheres to Protestant Christianity, making the Sumba Christian Church an important institution in preventing underage marriage in East Sumba. The research method used in this study is empirical juridical with primary data sourced from interviews. This study aims to determine the correlation between the policies of the Sumba Christian Church authorities and the prevention of child marriage in East Sumba Regency. Based on the results of the study, it was found that the Sumba Christian Church Synod as the church authority has formulated a policy for preventing underage marriage by accommodating underage marriage prevention and child protection programs in the church's work program and collaborating with other stakeholders including the Police PPA Unit, the Social Service, WVI, other synods, and inter-denominational churches in Sumba to implement underage marriage prevention programs. This policy is correlated with the prevention of child marriage in East Sumba Regency because with the participation of the Sumba Christian Church, the National Strategy for the Prevention of Underage Marriage can be implemented in East Sumba Regency.